2018
DOI: 10.1371/journal.pone.0196648
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices related to tuberculosis in pharmacy workers in a cross-sectional survey in El Agustino, Peru

Abstract: IntroductionAlthough the worldwide incidence of tuberculosis (TB) is slowly decreasing, annual infection rates in Peru remain among the highest in the Americas. Pharmacies could play an important role in facilitating early detection of TB. However, the awareness, expertise and cooperation of pharmacy workers is fundamental. This study explored the TB-related knowledge, attitudes and practices of pharmacy workers in a district with one of the highest incidences of TB in Peru.MethodsThis cross-sectional study ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
1
16
0
5
Order By: Relevance
“…[39][40][41][42] These findings show that, in developing countries such as Pakistan, low income, fewer resources and less healthcare facilities compel people to the inexpensive attainment of healthcare services. 43,44 In Pakistan, out-of-pocket expenditures for health are very high, so people find the non-prescription purchase of medicines as a cheaper alternative to avoid consultation fees and diagnostic expenditures. 39 Another Pakistani study showed that the cost of antibiotics with prescriptions lied in the range of Rs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[39][40][41][42] These findings show that, in developing countries such as Pakistan, low income, fewer resources and less healthcare facilities compel people to the inexpensive attainment of healthcare services. 43,44 In Pakistan, out-of-pocket expenditures for health are very high, so people find the non-prescription purchase of medicines as a cheaper alternative to avoid consultation fees and diagnostic expenditures. 39 Another Pakistani study showed that the cost of antibiotics with prescriptions lied in the range of Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were shown in a previous study conducted in Tanzania, where pharmacy workers stated financial gain as a motivating factor for providing medicines to the customers without a valid prescription. 44 It may be due to the reason that, in developing countries, pharmacies are business places and pharmacy workers always look for opportunities to sell their medicines. 44 Comprehensive instructions about medicines consist of information about their use as well as possible side effects, drug interactions, precautions, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Pengetahuan farmasis di Peru cukup baik, namun pengetahuan mengenai pencegahan dan penularan TB masih kurang. 21 Sebuah studi di Indonesia menunjukkan pengetahuan staf klinis yang kurang dalam hal pengendalian infeksi, seperti skrining batuk di antara pengunjung (38%) dan penggunaan masker pernapasan (48%). 22 Di Iran, pengetahuan para staf laboratorium TB lebih baik apabila dibandingkan pengetahuan staf laboratorium non-TB, mengingat bahwa tingkat pendidikan memiliki pengaruh yang signifikan terhadap pengetahuan.…”
Section: Pengetahuan Tenaga Kesehatan Terhadap Tbunclassified
“…20 Sikap serupa ditunjukkan oleh farmasis di Peru yakni mayoritas menyatakan bahwa mereka suka berbicara mengenai opsi perawatan dan merasa nyaman berbicara mengenai TB dengan klien meraka. 21 Studi di Indonesia menunjukkan staf klinis program TB dan staf lainnya menyatakan tertekan dan takut dalam melakukan perawatan MDR-TB. 22 Studi di Iran menunjukkan sikap staf laboratorium TB lebih positif dibanding sikap staf laboratorium non-TB.…”
Section: Sikap Tenaga Kesahatan Terhadap Tbunclassified